An ultralow-density aerogel foam concrete and a preparation method and application thereof
Patent Information
- Application Number
- CN202611421991.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-30
AI Technical Summary
一方面,常规改性方式无法实现微米闭孔气泡的稳定成型,气泡尺寸杂乱,大小孔无序分布,材料匀质性差
1、本发明提供的气凝胶泡沫混凝土通过纳米二氧化硅颗粒协同稳泡、改性泡沫精准适配水泥浆体,搭配疏水二氧化硅气凝胶颗粒的填充改性,精准调控气泡结构,使干密度低于416kg/m3,远低于常规泡沫混凝土密度标准,同时限定微米闭孔气泡孔径为100-400μm,气泡尺寸均匀、结构规整,构建了微米闭孔气泡和纳米介孔的多级隔热结构,相较于传统单一孔隙泡沫混凝土,保温隔热性能显著提升;
Smart Images

Figure CN123003227A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ultra-low density aerogel foam concrete technology, and in particular to an ultra-low density aerogel foam concrete, its preparation method, and its application. Background Technology
[0002] Foamed concrete is a lightweight, porous, novel inorganic thermal insulation building material. With its numerous advantages, including lightweight, thermal insulation, fire resistance, sound insulation, vibration damping, energy saving, environmental friendliness, and low cost, it is widely used in building energy conservation fields such as self-insulating blocks, exterior wall panels, and roof insulation. It is one of the core materials with the greatest development potential in current building insulation systems. As building energy conservation standards continue to upgrade, ultra-low density, ultra-high insulation, high strength, and high stability foamed concrete materials have become a key focus of industry research and development. The performance shortcomings of traditional foamed concrete are becoming increasingly prominent, making it difficult to meet the application requirements of high-end building energy conservation and prefabricated buildings.
[0003] Currently, conventional foamed concrete on the market generally suffers from high density and limited thermal insulation performance, with dry density mostly concentrated around 500 kg / m³. 3 As mentioned above, low-density products are highly susceptible to defects such as poor bubble stability, uneven pore size, and high open-cell ratio during the manufacturing process. Traditional foamed concrete bubbles are mostly open-pore structures with thin, incomplete walls, making them prone to collapse, merging, and rupture during molding and curing. This not only makes it difficult to further reduce the overall density of the material but also significantly increases its water absorption rate, compromising its thermal insulation performance and structural stability. Furthermore, conventional foamed concrete has a simple pore structure, lacking a multi-level nanoporous synergistic insulation structure. While its air convection heat transfer and solid-state heat conduction efficiency are high, its low-temperature insulation and long-term insulation effects are poor, and its performance is easily degraded by changes in temperature and humidity over long-term use.
[0004] In existing technologies, some studies have attempted to modify foamed concrete by adding aerogel, but most of these studies employ simple blending methods without precise control over the bubble structure and aerogel adhesion. On the one hand, conventional modification methods cannot achieve stable molding of micron-sized closed-cell bubbles, resulting in chaotic bubble sizes, disordered distribution of large and small pores, and poor material homogeneity. On the other hand, aerogel particles have weak bonding with the cement matrix, easily leading to agglomeration and detachment, failing to effectively adhere to the bubble walls and thus hindering the utilization of the thermal insulation advantages of nanoporous structures. This not only prevents ultra-low density molding but also wastes aerogel raw materials, significantly increasing production costs. Furthermore, traditional foamed concrete foaming systems have poor foam stabilization effects, lacking a synergistic foam stabilization mechanism with nanoparticles. During preparation, foam is prone to collapse, slurry stratification is severe, resulting in low finished product qualification rates, poor stability in large-scale production, and an inability to simultaneously achieve optimal mechanical and thermal insulation properties, severely limiting its application in high-end building insulation and prefabricated building envelopes.
[0005] In summary, existing foamed concrete suffers from technical defects such as high dry density, poor stability of bubble structure, unreasonable pore structure, insufficient thermal insulation performance, poor molding quality, and low cost-effectiveness. There is an urgent need to develop an aerogel foamed concrete with controllable structure, ultra-low density, excellent thermal insulation performance, and strong stability, as well as its preparation process, to solve many of the shortcomings of existing technologies and adapt to high-standard building energy-saving application scenarios. Summary of the Invention
[0006] The purpose of this invention is to provide an ultra-low density aerogel foam concrete, its preparation method, and its application, in order to solve the above-mentioned problems.
[0007] To achieve the above objectives, the present invention provides an ultra-low density aerogel foam concrete, comprising aerogel foam concrete and micron-sized closed-cell bubbles stabilized by nano-silica inside, wherein hydrophobic silica aerogel particles are attached to the pore walls of the micron-sized closed-cell bubbles, and the hydrophobic silica aerogel particles have nano-mesopores inside.
[0008] Preferably, the pore size of the micron-sized closed-cell air bubbles is 100-400 μm, and the dry density of the aerogel foam concrete is less than 416 kg / m³. 3 .
[0009] A method for preparing ultra-low density aerogel foam concrete includes the following steps: S1. Preparation of hydrophobic silica aerogel particles; S2. Disperse nano-silica particles ultrasonically in deionized water, add cement foaming agent and foam stabilizer, and stir evenly to obtain modified foam; S3. After mixing cement and water to obtain cement paste, add the modified foam in S2 and stir evenly. Then slowly add the hydrophobic silica aerogel particles in S1 and mix evenly to obtain aerogel foam concrete slurry. S4. Pour the aerogel foam concrete slurry from S3 into a mold, and after curing, obtain aerogel foam concrete.
[0010] Preferably, in step S1, tetraethyl orthosilicate, anhydrous ethanol, and deionized water are mixed and stirred until homogeneous. Hydrochloric acid is added to adjust the pH and stirring is continued. Ammonia water is slowly added dropwise to adjust the pH, and the mixture is allowed to stand at room temperature. The mixture is then placed in an aging solution and sealed for aging treatment for 20-30 hours. Solvent exchange is performed in hexane for 20-30 hours, followed by modification in a modification solution for 20-30 hours. The surface is then cleaned, dried at 70-90°C for 2-4 hours, and then dried at 100-150°C for 5-8 hours to obtain hydrophobic silica aerogel particles.
[0011] Preferably, in S1, the molar ratio of tetraethyl orthosilicate, anhydrous ethanol, and deionized water is 1:7:3; The aging solution is composed of anhydrous ethanol and tetraethyl orthosilicate, with a volume ratio of 4:1. The modification solution consists of trimethylchlorosilane and n-hexane, with the volume of trimethylchlorosilane being 8-12% of the modification solution. The modification temperature is 40-60℃, and the modification time is 20-28h.
[0012] Preferably, in S2, the mass of the nano-silica particles is 1.5-3.0% of the cement foaming agent, the ultrasonic dispersion frequency is 35-45kHz, and the ultrasonic dispersion time is 15-30min.
[0013] Preferably, in S2, the foam stabilizer includes hydroxypropyl methylcellulose, and the mass of the foam stabilizer is 0.5-1% of the modified foam; Cement foaming agents include plant protein composite foaming agents.
[0014] Preferably, in S3, the mass of the hydrophobic silica aerogel particles is 5-10% of the volume of the aerogel foam concrete, and the water-cement ratio of the cement is 0.4-0.5.
[0015] Preferably, in S3, 2-4% of the mass of aerogel foam concrete as a quick-setting agent and 0.10-0.20% of the mass of water as a thickener are also added.
[0016] An application of ultra-low density aerogel foam concrete is used in the preparation of self-insulating building blocks, non-load-bearing exterior wall panels, or roof insulation structural layers.
[0017] Therefore, the present invention employs the above-mentioned ultra-low density aerogel foam concrete, its preparation method, and its application, and its beneficial effects are as follows: 1. The aerogel foam concrete provided by this invention utilizes nano-silica particles to synergistically stabilize and modify the foam for precise adaptation to cement paste. Combined with the filling modification of hydrophobic silica aerogel particles, the bubble structure is precisely controlled, resulting in a dry density below 416 kg / m³. 3 The density is far lower than that of conventional foamed concrete. At the same time, the pore size of the micron-sized closed-cell bubbles is limited to 100-400μm. The bubbles are uniform in size and regular in structure, which creates a multi-level thermal insulation structure of micron-sized closed-cell bubbles and nano-mesopores. Compared with traditional single-pore foamed concrete, the thermal insulation performance is significantly improved. 2. This invention uses nano-silica particles to modify foam, and achieves uniform distribution of nano-particles through ultrasonic dispersion. Relying on the interface enhancement effect of nano-silica particles, the foam film wall strength is greatly improved, and long-term stability of micron-sized closed-cell bubbles is achieved. 3. This invention uses trimethylchlorosilane to hydrophobically modify silica aerogel, giving the silica aerogel particles attached to the pore walls excellent hydrophobic properties. This effectively prevents external moisture and water vapor from penetrating into the concrete, avoiding problems such as failure of thermal insulation performance and freeze-thaw damage to the matrix caused by water absorption in the pores.
[0018] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0019] Figure 1 These are combined SEM images of foamed concrete from Embodiments 1-2 and Comparative Examples 1-2 of the present invention, wherein... Figure 1 Image (a) in the diagram is the SEM image from Comparative Example 1. Figure 1 (b) is the SEM image from Comparative Example 2. Figure 1 (c) is the SEM image from Example 1. Figure 1 (d) in the figure is the SEM image from Example 2; Figure 2 These are combined appearance diagrams of the hydrophobic silica aerogel particles in Embodiment 1 and Comparative Examples 3-6 of the present invention, wherein... Figure 2 Image (a) is an image showing the appearance of the hydrophobic silica aerogel particles in Example 1. Figure 2 Image (b) shows the appearance of the hydrophobic silica aerogel particles in Comparative Example 3. Figure 2 Image (c) shows the appearance of the hydrophobic silica aerogel particles in Comparative Example 4. Figure 2 Image (d) shows the appearance of the hydrophobic silica aerogel particles in Comparative Example 5. Figure 2 (e) in the figure is an image of the hydrophobic silica aerogel particles in Comparative Example 6. Figure 3 These are SEM composite images of the hydrophobic silica aerogel particles in Embodiment 1, Comparative Examples 3-4, and Comparative Example 6 of the present invention, wherein... Figure 3 Image (a) is a SEM image of the hydrophobic silica aerogel particles in Example 1. Figure 3 Image (b) in the image is a SEM image of the hydrophobic silica aerogel particles in Comparative Example 3. Figure 3 Image (c) in the figure is a SEM image of the hydrophobic silica aerogel particles in Comparative Example 4. Figure 3 (d) is the SEM image of the hydrophobic silica aerogel particles in Comparative Example 6. Detailed Implementation
[0020] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.
[0021] This invention provides an ultra-low density aerogel foam concrete, comprising aerogel foam concrete and micron-sized closed-cell air bubbles stabilized by nano-silica within it. The pore walls of the micron-sized closed-cell air bubbles are attached with hydrophobic silica aerogel particles, which contain nano-mesopores. By introducing a large number of micron-sized closed-cell air bubbles and nano-sized mesoporous aerogel particles, the mass per unit volume of the aerogel foam concrete is significantly reduced. The hierarchical pore structure of the micron-sized air bubbles and the mesopores of the nano-sized hydrophobic silica aerogel particles significantly extends the solid heat conduction path, and the stagnant air within the hydrophobic silica aerogel framework blocks convective heat transfer. The hydrophobic silica aerogel adheres to the surface of the air bubble pore walls, forming a waterproof barrier; simultaneously, the nano-silica (NS) stabilizes the closed-cell structure, reducing interconnected pores and preventing capillary penetration of water, resulting in a water absorption rate ≤64%.
[0022] In some embodiments of the present invention, the pore size of the micron-sized closed-cell bubbles is 100-400 μm, and the dry density of the aerogel foam concrete is less than 416 kg / m³. 3 NS particles adsorbed at the bubble interface increase the liquid film strength, and the hydrophobic silica aerogel itself has a three-dimensional mesoporous network.
[0023] A method for preparing ultra-low density aerogel foam concrete includes the following steps: S1. Preparation of hydrophobic silica aerogel particles; S2. Disperse nano-silica particles ultrasonically in deionized water, add cement foaming agent and foam stabilizer, and stir evenly to obtain modified foam; after ultrasonic dispersion, nano-silica particles adsorb onto the gas-liquid interface of bubbles, increasing the viscoelasticity and mechanical strength of the interface film and inhibiting bubble aggregation.
[0024] S3. After mixing cement and water to obtain cement paste, add the modified foam from S2 and stir evenly. Then slowly add the hydrophobic silica aerogel particles from S1 and mix evenly to obtain aerogel foam concrete slurry. First, add the modified foam to ensure that the air bubbles are evenly distributed in the slurry. Then add the hydrophobic silica aerogel particles (directly added without pre-constructing a 3D printed skeleton structure) to avoid high shear stirring from damaging the skeleton. The hydrophobic silica aerogel particles are pinned to the surface of the pore wall rather than filling the inside of the air bubbles because of their hydrophobicity.
[0025] S4. Pour the aerogel foam concrete slurry from S3 into a mold, and after curing, obtain aerogel foam concrete.
[0026] In some embodiments of the present invention, in step S1, tetraethyl orthosilicate (TEOS), anhydrous ethanol, and deionized water are mixed and stirred until homogeneous. Hydrochloric acid is added to adjust the pH, and stirring continues. Ammonia is slowly added dropwise to adjust the pH, and the mixture is allowed to stand at room temperature. It is then placed in an aging solution and sealed for aging treatment for 20-30 hours. Solvent exchange in hexane is performed for 20-30 hours, followed by modification in a modification solution for 20-30 hours. The surface is then cleaned, dried first at 70-90°C for 2-4 hours, and then dried at 100-150°C for 5-8 hours to obtain hydrophobic silica aerogel particles. During drying, most of the solvent is slowly removed at 70-90°C to reduce capillary stress caused by vigorous vaporization; at 100-150°C, residual bound water is completely removed, and the framework is further cross-linked. Compared to direct isothermal drying at 100°C, which leads to framework collapse and densification, segmented drying ensures the aerogel remains intact and porous with minimal shrinkage.
[0027] In some embodiments of the present invention, in S1, the molar ratio of tetraethyl orthosilicate, anhydrous ethanol and deionized water is 1:7:3; The aging solution is composed of anhydrous ethanol and tetraethyl orthosilicate, with a volume ratio of 4:1. The modification solution consists of trimethylchlorosilane and n-hexane, with the volume of trimethylchlorosilane (TMCS) being 8-12% of the modification solution. The modification temperature is 40-60℃, and the modification time is 20-28 hours. If the TMCS concentration is too low (e.g., 5%), the hydrophobic coverage will be insufficient, leading to capillary shrinkage during drying. A suitable temperature ensures proper reaction kinetics and avoids insufficient reaction at low temperatures (30℃), which could result in insufficient skeleton strength.
[0028] In some embodiments of the present invention, in step S2, the mass of the nano-silica particles is 1.5-3.0% of the cement foaming agent, the ultrasonic dispersion frequency is 35-45 kHz, and the ultrasonic dispersion time is 15-30 min. The particle size of the nano-silica particles is 25-35 nm. Nanoparticles in this size range have high surface energy and can effectively anchor to the bubble film; the ultrasonic frequency avoids agglomeration and ensures monodispersity of NS.
[0029] In some embodiments of the present invention, in S2, the foam stabilizer includes hydroxypropyl methylcellulose (HPMC), and the mass of the foam stabilizer is 0.5-1% of the modified foam; HPMC, as a nonionic foam stabilizer, reduces the bubble migration rate through the dual effects of thickening and surface activity.
[0030] Cement foaming agents include plant protein composite foaming agents.
[0031] In some embodiments of the present invention, in S3, the mass of the hydrophobic silica aerogel particles is 5-10% of the volume of the aerogel foam concrete, and the water-cement ratio of the cement is 0.4-0.5.
[0032] In some embodiments of the present invention, in step S3, 2-4% by weight of the aerogel foam concrete quick-setting agent and 0.10-0.20% by weight of the water thickener are also added. The quick-setting agent (made by mixing bauxite, soda ash, and quicklime and then firing at high temperature) accelerates the hydration of C3S, causing the slurry to quickly lose its fluidity before the aerogel floats up; the thickener increases the yield stress of the slurry and physically binds the lightweight particles.
[0033] An application of ultra-low density aerogel foam concrete is used in the preparation of self-insulating building blocks, non-load-bearing exterior wall panels, or roof insulation structural layers.
[0034] The following reagents are used in this invention: Ethyl orthosilicate: purchased from Aladdin, purity ≥99%; Anhydrous ethanol: purchased from Yisheng Chemical Co., Ltd., purity ≥99.7%; n-Hexane: Purchased from Shanghai Lingfeng Reagent, purity ≥97%; Trimethylchlorosilane: purchased from Aladdin, purity ≥98%; Hydrochloric acid: purchased from Sinopharm Chemical Reagent Co., Ltd., concentration 36-38%; Ammonia solution: purchased from Shanghai Lingfeng Reagent, concentration 25-28%; Nano-silica particles: purchased from Ron Company, with a particle size of 30±5nm; PII52.5 grade Portland cement: purchased from Nanjing Onoda Cement Co., Ltd., apparent density 3.13 g•cm³. -3 The CaO content is approximately 63%. Hydroxypropyl methylcellulose: purchased from McLean, viscosity 20000 mPa⸳s; Grey Ba concrete quick-setting agent: purchased from Hongxiang Building Admixture Factory, Laiyang City, Shandong Province; CO-6130 cement thickening powder: purchased from Guangdong Nanhui New Materials Co., Ltd., density approximately 1.39 g / cm³. 3 .
[0035] Example 1 S1. Preparation of hydrophobic silica aerogel particles: Tetraethyl orthosilicate, anhydrous ethanol, and deionized water were mixed in a molar ratio of 1:7:3 and stirred for 30 minutes until homogeneous. Hydrochloric acid was added to adjust the pH to strongly acidic (pH 2.5), and stirring continued until complete hydrolysis to form a silica sol. 0.5 mol / L ammonia was slowly added dropwise to adjust the pH to neutral. The mixture was allowed to stand at room temperature for gelation. It was then placed in an aging solution (anhydrous ethanol and tetraethyl orthosilicate volume ratio of 4:1) and sealed for 24 hours at 50°C for aging. Solvent exchange was then performed in hexane at 50°C for 24 hours. Afterward, modification was carried out in a modification solution (trimethylchlorosilane and hexane, with trimethylchlorosilane comprising 10% of the modification solution) at 50°C for 24 hours. The surface was then cleaned with hexane. The mixture was first dried at 80°C for 3 hours, then dried at 120°C for 6 hours to obtain hydrophobic silica aerogel particles with a water contact angle of 151°.
[0036] S2. Disperse the nano-silica particles in deionized water at a frequency of 40kHz for 30 minutes. The mass of the nano-silica particles is 2% of the cement foaming agent. Add the cement foaming agent (plant protein composite foaming agent) and foam stabilizer (hydroxypropyl methylcellulose, mass of 1% of the modified foam) and stir evenly to obtain the modified foam.
[0037] S3. Dissolve 3% (by weight of the aerogel foam concrete) of the quick-setting agent and 0.15% (by weight of the water) of the thickener in water (98.63 kg) to obtain an aqueous solution. Mix 219.63 kg of PII 52.5 grade Portland cement (water-cement ratio 0.45) with the aqueous solution to obtain a cement paste. Add 0.781 m... 3 The modified foam in S2 is stirred evenly, and then 8 kg of hydrophobic silica aerogel particles from S1 (5% of the volume of aerogel foam concrete) are slowly added. After mixing evenly, aerogel foam concrete slurry is obtained.
[0038] S4. Pour the aerogel foam concrete slurry from S3 into a mold, and after curing, obtain aerogel foam concrete.
[0039] Example 2 S1. Preparation of hydrophobic silica aerogel particles: Tetraethyl orthosilicate, anhydrous ethanol, and deionized water were mixed in a molar ratio of 1:7:3 and stirred for 30 minutes until homogeneous. Hydrochloric acid was added to adjust the pH to strongly acidic (pH 2.5), and stirring continued until complete hydrolysis to form a silica sol. 0.5 mol / L ammonia was slowly added dropwise to adjust the pH to neutral. The mixture was allowed to stand at room temperature for gelation. It was then placed in an aging solution (anhydrous ethanol and tetraethyl orthosilicate volume ratio of 4:1) and sealed for 24 hours at 50°C for aging. Solvent exchange was then performed in hexane at 50°C for 24 hours. Afterward, modification was carried out in a modification solution (trimethylchlorosilane and hexane, with trimethylchlorosilane comprising 10% of the modification solution) at 50°C for 24 hours, followed by surface cleaning with hexane. The mixture was first dried at 80°C for 3 hours, then dried at 120°C for 6 hours to obtain hydrophobic silica aerogel particles with a water contact angle of 151°.
[0040] S2. Disperse the nano-silica particles in deionized water at a frequency of 40kHz for 30 minutes. The mass of the nano-silica particles is 2% of the cement foaming agent. Add the cement foaming agent, plant protein composite foaming agent, and foam stabilizer, hydroxypropyl methylcellulose (mass of 1% of the modified foam), and stir evenly to obtain the modified foam.
[0041] S3. Dissolve 3% (by weight) of the accelerator (Huiba concrete accelerator) and 0.15% (by weight) of the thickener (CO-6130 cement thickener powder) in water (69.59 kg) to obtain an aqueous solution. Mix 154.65 kg of PII 52.5 grade Portland cement (water-cement ratio 0.45) with the aqueous solution to obtain a cement paste. Add 0.781 m... 3 The modified foam in S2 is stirred evenly, and then 10% of the volume of hydrophobic silica aerogel particles (16 kg) in S1 is slowly added. After mixing evenly, the aerogel foam concrete slurry is obtained.
[0042] S4. Pour the aerogel foam concrete slurry from S3 into a mold, and after curing, obtain aerogel foam concrete.
[0043] Comparative Example 1 S1. Mix cement foaming agent (plant protein composite foaming agent) and foam stabilizer (hydroxypropyl methylcellulose, 1% of the modified foam by mass) evenly to obtain modified foam.
[0044] S2. Dissolve 3% (by weight of concrete) of quick-setting agent and 0.15% (by weight of water) of thickener in water (150 kg) to obtain an aqueous solution. Mix 333 kg of PII 52.5 grade Portland cement (water-cement ratio 0.45) with the aqueous solution to obtain a cement paste. Add 0.781 m... 3 The modified foam in S1 is stirred evenly to obtain foamed concrete slurry.
[0045] S3. Pour the concrete slurry from S2 into a mold, and after curing, obtain concrete.
[0046] Comparative Example 2 S1. Disperse nano-silica particles in deionized water at a frequency of 40kHz for 30 minutes. The mass of nano-silica particles is 2% of the cement foaming agent. Add cement foaming agent (plant protein composite foaming agent) and foam stabilizer (hydroxypropyl methylcellulose, mass of 1% of the modified foam) and stir evenly to obtain modified foam.
[0047] S2. Dissolve 3% (by weight of concrete) of quick-setting agent and 0.15% (by weight of water) of thickener in water (150 kg) to obtain an aqueous solution. Mix 333 kg of PII 52.5 grade Portland cement (water-cement ratio 0.45) with the aqueous solution to obtain a cement paste. Add 0.781 m... 3 The modified foam in S1 is stirred evenly to obtain foamed concrete slurry.
[0048] S3. The foamed concrete slurry in S2 is poured into a mold and cured to obtain aerogel foamed concrete.
[0049] Comparative Example 3 Tetraethyl orthosilicate, anhydrous ethanol, and deionized water were mixed in a molar ratio of 1:7:3 and stirred for 30 minutes until homogeneous. Hydrochloric acid was added to adjust the pH to strongly acidic (pH 2.5), and stirring continued until complete hydrolysis to form a silica sol. Concentrated ammonia was slowly added dropwise to adjust the pH to neutral (pH 7), and the mixture was allowed to stand at room temperature for gelation. The mixture was then placed in an aging solution (anhydrous ethanol and tetraethyl orthosilicate volume ratio of 4:1) and sealed for 24 hours at 50°C for aging. Solvent exchange was then performed in hexane at 50°C for 24 hours. Afterward, modification was carried out in a modification solution (trimethylchlorosilane and hexane, with trimethylchlorosilane comprising 10% of the modification solution) at 50°C for 24 hours, followed by surface cleaning with hexane. The mixture was first dried at 80°C for 3 hours, then dried at 120°C for 6 hours to obtain hydrophobic silica aerogel particles.
[0050] Comparative Example 4 Tetraethyl orthosilicate, anhydrous ethanol, and deionized water were mixed in a molar ratio of 1:7:3 and stirred for 30 minutes until homogeneous. Hydrochloric acid was added to adjust the pH to strongly acidic (pH 2.5), and stirring continued until complete hydrolysis to form a silica sol. 0.5 mol / L ammonia was slowly added dropwise to adjust the pH to neutral (pH 7), and the mixture was allowed to stand at room temperature for gelation. The mixture was then placed in an aging solution (anhydrous ethanol and tetraethyl orthosilicate volume ratio of 4:1) and sealed for 24 hours at 30°C for aging. Solvent exchange was then performed in hexane at 30°C for 24 hours. Afterward, modification was carried out in a modification solution (trimethylchlorosilane and hexane, with trimethylchlorosilane comprising 10% of the modification solution) at 30°C for 24 hours, followed by surface cleaning with hexane. The mixture was first dried at 80°C for 3 hours, then dried at 120°C for 6 hours to obtain hydrophobic silica aerogel particles with a water contact angle of 142°.
[0051] Comparative Example 5 Tetraethyl orthosilicate, anhydrous ethanol, and deionized water were mixed in a molar ratio of 1:7:3 and stirred for 30 minutes until homogeneous. Hydrochloric acid was added to adjust the pH to strongly acidic (pH 2.5), and stirring continued until complete hydrolysis to form a silica sol. 0.5 mol / L ammonia was slowly added dropwise to adjust the pH to neutral (pH 7), and the mixture was allowed to stand at room temperature for gelation. The mixture was then placed in an aging solution (anhydrous ethanol and tetraethyl orthosilicate volume ratio of 4:1) and sealed for 24 hours at 50°C for aging. Solvent exchange was then performed in hexane at 50°C for 24 hours. Afterward, modification was carried out in a modification solution (trimethylchlorosilane and hexane, with trimethylchlorosilane comprising 5% of the modification solution) at 50°C for 24 hours, followed by surface cleaning with hexane. The mixture was first dried at 80°C for 3 hours, then dried at 120°C for 6 hours to obtain hydrophobic silica aerogel particles with a water contact angle of 127°.
[0052] Comparative Example 6 Tetraethyl orthosilicate, anhydrous ethanol, and deionized water were mixed in a molar ratio of 1:7:3 and stirred for 30 minutes until homogeneous. Hydrochloric acid was added to adjust the pH to strongly acidic (pH 2.5), and stirring continued until complete hydrolysis to form a silica sol. 0.5 mol / L ammonia was slowly added dropwise to adjust the pH to neutral. The mixture was allowed to stand at room temperature for gelation. It was then placed in an aging solution (anhydrous ethanol and tetraethyl orthosilicate volume ratio of 4:1) and sealed for 24 hours at 50°C for aging. Solvent exchange was then performed in hexane at 50°C for 24 hours. Afterward, modification was carried out in a modification solution (trimethylchlorosilane and hexane, with trimethylchlorosilane comprising 10% of the modification solution) at 50°C for 24 hours. The surface was then cleaned with hexane. The mixture was dried at 100°C for 6 hours to obtain hydrophobic silica aerogel particles.
[0053] Performance testing a. SEM tests were performed on the foamed concrete in Examples 1-2 and Comparative Examples 1-2, and the results are as follows: Figure 1 As shown. By Figure 1 (a) and Figure 1As shown in (b), compared with Comparative Example 1, the incorporation of nano-silica particles in Comparative Example 2 can reduce the generation of macropores, lower the average pore size, and optimize the pore structure. NS particles adsorb at the closed-cell bubble liquid film, which can inhibit bubble aggregation and coarsening, and improve the strength and stability of the foam. The higher the foam stability, the smaller the pore size can be during slurry mixing, making the pore distribution more uniform, thereby improving the matrix morphology. With the addition of NS particles, the pore structure of the foamed concrete sample shows a significant optimization trend. The pore shape becomes more regular and round, the pore size is more uniform, and the number of interconnected pores is significantly reduced. The pore wall structure is also more compact. It can be seen that NS has the effect of improving foam stability and optimizing pore structure. The adsorption of NS particles at the bubble liquid film inhibits bubble breakage and merging. At the same time, its pozzolanic activity participates in the hydration reaction, and the generated CSH gel fills the micropores, further densifying the pore walls.
[0054] Depend on Figure 1 (c) and Figure 1 As shown in (d), after incorporating hydrophobic silica aerogel particles, it is evident that these particles adhere to the pore walls. Further magnification reveals that the hydrophobic silica aerogel particles are fixed to the pore walls by hydration products. When the dosage of hydrophobic silica aerogel particles increases from 5% to 10%, the proportion of interconnected pores within the aerogel foam concrete increases, and the pore size distribution becomes more dispersed and less concentrated. This is mainly because excessive hydrophobic silica aerogel particles tend to agglomerate in the slurry, forming weak interfaces between the agglomerates, thus widening the pore size distribution range.
[0055] b. The following tests were performed on the concrete in Examples 1-2 and Comparative Examples 1-2, and the results are shown in Table 1: Compressive strength test: Refer to JG / T266-2011.
[0056] Flexural strength test: Before testing, three dry foamed concrete specimens were taken, using prism specimens with dimensions of 40mm×40mm×160mm and a loading rate of 50N / s. For compressive strength testing, cubic specimens with dimensions of 40mm×40mm×40mm were used, with a loading rate of 500N / s. Three specimens were taken for each test group, and the final result was expressed as the arithmetic mean of the measured values of all specimens.
[0057] Dry density test: Refer to JG / T266-2011.
[0058] Thermal conductivity test: IMDRY3001-Ⅱ-3594 thermal conductivity meter was used. The test method was in accordance with GB / T10294-2008. The specifications of the dried specimen were 300mm×300mm×30mm, with the cold plate set at 15℃ and the hot plate set at 35℃.
[0059] Flowability test: Refer to JGJ / T341-2014. The test device consists of an open cylinder with an inner diameter and height of 80mm and a flat, horizontal and non-absorbent plastic base plate. After pouring in the slurry, let it stand for 1 minute until the slurry flow basically stops. Then, use a ruler to measure the maximum diameter of the slurry after it is spread.
[0060] Table 1 Performance data of Examples 1-2 and Comparative Examples 1-2
[0061] c. The following tests were performed on the hydrophobic silica aerogel particles in Example 1 and Comparative Examples 3-6: The appearance of the hydrophobic silica aerogel particles in Example 1 and Comparative Examples 3-6 is as follows: Figure 2 As shown. By Figure 2 As can be seen in (a) of Example 1, the hydrophobic silica aerogel particles exhibit a pale blue, semi-transparent, irregular blocky structure. Figure 2 As can be seen in (b) of Comparative Example 3, the hydrophobic silica aerogel particles changed from translucent blocks to milky white, rough-surfaced blocks. This is because the increased ammonia concentration significantly accelerated the polymerization rate, causing the wet gel network to form rapidly and the degree of cross-linking to increase, resulting in more residual hydroxyl groups. During drying, volume shrinkage and increased internal stress ultimately led to decreased transparency, and the shrinkage deformation caused internal stress concentration, making the particles brittle. Figure 2 As can be seen in (c) of Comparative Example 4, the integrity of the hydrophobic silica aerogel particles deteriorates, their transparency decreases, and their morphological regularity is significantly worse than that of the sample prepared at 50℃. They are also more brittle and prone to breakage during the mixing of foamed concrete, making them unsuitable for preparing ultra-low density foamed concrete. This is because the reaction and cross-linking processes slow down at lower temperatures, resulting in insufficient strength of the wet gel skeleton, making it more susceptible to significant volume shrinkage and stress cracking during subsequent drying. Figure 2 As can be seen in (d) of Comparative Example 5, the density of hydrophobic silica aerogel particles is significantly increased. This is because the decrease in TMCS concentration reduces the substitution degree of silanol groups on the wet gel surface, weakening hydrophobicity. During the drying process, capillary forces are more likely to induce skeleton shrinkage and collapse, resulting in a significant increase in aerogel density and more prominent cracking and shrinkage phenomena. Relatively high-density aerogels are not suitable for the preparation of ultra-low-density foamed concrete. Figure 2As can be seen from (e) in Comparative Example 6, the hydrophobic silica aerogel particles were heated too quickly and the temperature gradient changed. The solvent removal rate inside the wet gel was not smooth enough, which led to an increase in the capillary stress on the skeleton during the drying process. The prepared hydrophobic silica aerogel particles had increased shrinkage, significantly increased density, decreased transparency, and severe cracking, exhibiting the densification characteristics of dry gel. The low porosity of the aerogel is also not conducive to the preparation of ultra-low density foamed concrete.
[0062] SEM analysis was performed on the hydrophobic silica aerogel particles in Examples 1, 3-4, and 6. The results are as follows: Figure 3 As shown. By Figure 3 As can be seen in (a) of Example 1, the structure exhibits a three-dimensional network. Its framework is composed of uniformly sized nanoscale colloidal particles that are stacked and connected to form a continuous and loose three-dimensional network structure. This network is filled with gas, exhibiting a loose and porous morphology. Further observation reveals that the gel particles are interconnected to form pores. These pores are relatively uniform in size, regularly distributed, and interconnected, forming a three-dimensionally connected porous system. Figure 3 As shown in (b) of Comparative Example 3, the agglomeration of particles was significantly intensified, the particle size distribution widened, and the originally continuous and uniform three-dimensional network structure became rough and irregular. This indicates that the high concentration of ammonia significantly increased the pH value of the system, greatly accelerating the condensation reaction rate. In a very short time, the silanol monomers rapidly polymerized and excessively cross-linked, causing the nanoparticles to agglomerate disorderly before they could arrange themselves in an orderly manner, forming locally dense particle clusters. This non-uniform agglomeration behavior disrupted the uniformity and continuity of the three-dimensional network, resulting in uneven pore size distribution, and even macropore blockage and poor pore connectivity in some areas, leading to a deterioration of the overall pore structure. Figure 3 As shown in (c), although Comparative Example 4 still maintains a basic three-dimensional network framework, significant structural collapse and dense particle packing have occurred in local areas. This is because the reaction kinetics of aging, solvent exchange, and hydrophobic modification processes are significantly reduced under low-temperature conditions. During the aging stage, further cross-linking and reinforcement of the gel network are insufficient, resulting in lower framework strength; solvent exchange efficiency decreases, making it difficult to completely replace residual water and ethanol within the pores; and the reaction between the modifier and silanol groups is incomplete, leading to a decrease in surface hydrophobic coverage. This weakens the gel's ability to resist capillary stress during subsequent atmospheric pressure drying, causing some pore walls to collapse inward due to shrinkage stress, leading to pore blockage and increased surface roughness. Figure 3As can be seen in (d) of Comparative Example 6, the continuous porous network morphology characteristic of aerogels has been completely lost. The particles are tightly packed with almost no obvious pores between them, exhibiting the characteristics of a dense, blocky dry gel. Due to the use of a single high-temperature drying process (100℃) without a low-temperature pre-drying stage, the solvent in the pores of the wet gel evaporates rapidly at the high temperature, generating enormous capillary pressure. The gel network is instantly destroyed because it cannot shrink in time, and the skeleton undergoes irreversible collapse and densification.
[0063] Therefore, this invention employs the aforementioned ultra-low density aerogel foam concrete, its preparation method, and its application. The aerogel foam concrete utilizes nano-silica particles to synergistically stabilize and modify the foam for precise adaptation to cement paste. Combined with the filling modification of hydrophobic silica aerogel particles, the bubble structure is precisely controlled, resulting in a dry density below 416 kg / m³. 3 It is far below the density standard of conventional foamed concrete.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. An ultra-low density aerogel foam concrete, characterized in that: It includes aerogel foam concrete and its interior composed of micron-sized closed-cell air bubbles stabilized by nano-silica. The pore walls of the micron-sized closed-cell air bubbles are attached with hydrophobic silica aerogel particles, and the hydrophobic silica aerogel particles contain nano-mesoporous structures.
2. The ultra-low density aerogel foam concrete according to claim 1, characterized in that: The pore size of micron-sized closed-cell air bubbles is 100-400μm, and the dry density of aerogel foam concrete is less than 416kg / m³. 3 .
3. A method for preparing ultra-low density aerogel foam concrete, characterized in that: The preparation of aerogel foam concrete as described in any one of claims 1-2 comprises the following steps: S1. Preparation of hydrophobic silica aerogel particles; S2. Disperse nano-silica particles ultrasonically in deionized water, add cement foaming agent and foam stabilizer, and stir evenly to obtain modified foam; S3. After mixing cement and water to obtain cement paste, add the modified foam in S2 and stir evenly. Then slowly add the hydrophobic silica aerogel particles in S1 and mix evenly to obtain aerogel foam concrete slurry. S4. Pour the aerogel foam concrete slurry from S3 into a mold, and after curing, obtain aerogel foam concrete.
4. The method for preparing ultra-low density aerogel foam concrete according to claim 3, characterized in that: In S1, tetraethyl orthosilicate, anhydrous ethanol, and deionized water are mixed and stirred until homogeneous. Hydrochloric acid is added to adjust the pH and stirring is continued. Ammonia water is slowly added dropwise to adjust the pH and then allowed to stand at room temperature. The mixture is then placed in an aging solution and sealed for aging treatment for 20-30 hours. Solvent exchange is performed in hexane for 20-30 hours, followed by modification in a modification solution for 20-30 hours. The surface is then cleaned and dried at 70-90℃ for 2-4 hours, and then at 100-150℃ for 5-8 hours to obtain hydrophobic silica aerogel particles.
5. The method for preparing ultra-low density aerogel foam concrete according to claim 4, characterized in that: In S1, the molar ratio of tetraethyl orthosilicate, anhydrous ethanol, and deionized water is 1:7:
3. The aging solution is composed of anhydrous ethanol and tetraethyl orthosilicate, with a volume ratio of 4:
1. The modification solution consists of trimethylchlorosilane and n-hexane, with the volume of trimethylchlorosilane being 8-12% of the modification solution. The modification temperature is 40-60℃, and the modification time is 20-28h.
6. The method for preparing ultra-low density aerogel foam concrete according to claim 3, characterized in that: In S2, the mass of nano-silica particles is 1.5-3.0% of the cement foaming agent, the ultrasonic dispersion frequency is 35-45kHz, and the ultrasonic dispersion time is 15-30min.
7. The method for preparing ultra-low density aerogel foam concrete according to claim 3, characterized in that: In S2, the foam stabilizer includes hydroxypropyl methylcellulose, and the mass of the foam stabilizer is 0.5-1% of the modified foam. Cement foaming agents include plant protein composite foaming agents.
8. The method for preparing ultra-low density aerogel foam concrete according to claim 3, characterized in that: In S3, the mass of hydrophobic silica aerogel particles is 5-10% of the volume of aerogel foam concrete, and the water-cement ratio of cement is 0.4-0.
5.
9. The method for preparing ultra-low density aerogel foam concrete according to claim 3, characterized in that: In S3, 2-4% of the aerogel foam concrete mass of quick-setting agent and 0.10-0.20% of the water mass of thickener are also added.
10. An application of ultra-low density aerogel foam concrete, characterized in that: The aerogel foam concrete according to any one of claims 1-2 is used in the preparation of self-insulating building blocks, non-load-bearing exterior wall panels or roof insulation structural layers.